2017
DOI: 10.1186/s11671-017-2344-x
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon Fibers “Thickly Overgrown” by Ag Nanohair Through Self-Assembly and Rapid Thermal Annealing

Abstract: Anisotropic nanomaterial-modified carbon fibers attract increasing attention because of their superior properties over traditional ones. In this study, activated carbon fibers (ACFs) “thickly overgrown” by Ag nanohair were prepared through self-assembly and rapid thermal annealing. Viscose fibers with well-dispersed silver nanoparticles (AgNPs) on surfaces were first prepared through self-assembly of hyperbranched poly(amino-amine) (HBPAA)-capped AgNPs on viscose surfaces. HBPAA endowed the AgNP surfaces with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…It is well known that pristine ACFs possess good thermal stability. 43 In this study, the ACFs exhibited weight loss of approximately 7% when the temperature reached 800 C, indicating excellent thermal stability. However, the TG curve of the DA-ACFs showed that a weight loss of approximately 5% occurred from 100 C to 180 C, which was caused by vaporization of the water bound to the bers.…”
Section: Tg Analysismentioning
confidence: 57%
“…It is well known that pristine ACFs possess good thermal stability. 43 In this study, the ACFs exhibited weight loss of approximately 7% when the temperature reached 800 C, indicating excellent thermal stability. However, the TG curve of the DA-ACFs showed that a weight loss of approximately 5% occurred from 100 C to 180 C, which was caused by vaporization of the water bound to the bers.…”
Section: Tg Analysismentioning
confidence: 57%
“…XPS was conducted to detect the surface chemistry of the ZnO@C composites. The survey spectra displayed in Supplementary Figure 4A confirmed that ZnO@C was composed of Zn, O, and C. Figure 2B shows the high-resolution Zn 2p spectrum with two obvious peaks at 1022 and 1045 eV, corresponding to the 2p 3/2 and 2p 1/2 of Zn, respectively [16] . The C 1s spectrum is shown in Figure 2C, where the peak at 284.5 eV was associated with sp 2 carbon.…”
Section: Resultsmentioning
confidence: 73%